ASSESSMENT OF SLEEP QUALITY AND PATTERNS SUGGESTIVE OF SOMNIOPATHIES AMONG STUDENTS OF ARMY MEDICAL COLLEGE, RAWALPINDI: Sleep Quality And Patterns Suggestive of Somniopathies - Nadeem, Dr Amina; Cheema, Maryam Khalid; Naseer, Maryum; Javed, Hamra (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess sleep quality and sleep patterns among students of Army Medical College, Rawalpindi.Study Design: Cross sectional study.Place and Duration of Study: Army Medical College, Rawalpindi, from Mar to May 2017.Material and Methods: Pittsburgh sleep quality index (PSQI) questionnaire was administered to a total of 567students. PSQI component and global scores of male and female students were statistically correlated. Excel 2013was used for statistical analysis of the collected data.Results: Out of the 567 administered questionnaires, complete responses amounted to 362 (Response Rate:63.8%); among them, 217 (60%) were females and 145 (40%) were males. Class-wise distribution of the studentswas as follows: 170 (47%) students from 1st year, 140 (38.7%) from 2nd year, 32 (8.8%) from 4th year and 20 (5.5%)from final year. Mean age of the participants was 19.57 ± 1.48 years (range: 17-25 years). Overall, 124 (34%)students were bracketed as ‘Good Sleepers’ whereas 238 (66%) fell into the category of ‘Poor Sleepers’ with amean PSQI score of 6.67 ± 2.275. This percentage frequency distribution and mean PSQI score did not differsignificantly (p=0.33) between genders. Female students reported significantly lower sedative usage (p